Host preference of tsetse: An important tool to appraise the Nagana risk of cattle in the cotton zone of Mali - Hoppenheit, A.; Steuber, S.; Bauer, B.; Ouma, E.M.; Diall, O.; Zessin, K.H.; Clausen, Peter-Henning (Springer, 2010)
Nagana, a vector-borne epizootic caused by trypanosomes, severely constrains the use of draught animals in the cotton zone of south-eastern Mali. The disease causes considerable economic losses for the local farmers due to high mortality and morbidity ensuing productivity losses. Nagana is routinely controlled by the use of trypanocides and an overreliance on their use throughout past decades resulted in multiple drug resistance of trypanosomes in most parts of West Africa's cotton belt. Designing alternative, effective vector control strategies requires an identification of the preferred hosts of tsetse flies through blood meal analysis as a prerequisite for estimating infection risk. A survey was, therefore, conducted between November 2008 and April 2009, catching 474 Glossina species which were dissected. Blood meals were smeared on filter paper (Whatman®-FTA-Cards) for laboratory analysis. DNA extractions and amplification using universal vertebrate cytochrome b primers of 120 assorted samples detected 74 DNA-containing specimens. The subsequent use of cattle-specific primers yielded 52 visible amplicons in the gel electrophoresis. Sequencing and BLASTN® analysis of the remaining samples revealed 19 blood meals matching with existing sequences of the human genome in Genbank®. Two samples originated from crocodiles whereas one was unidentifiable.